Spontaneous carrier generation and low recombination in high-efficiency non-fullerene solar cells. Issue 8 (14th July 2022) - Zhou, Guanqing; Zhang, Ming; Xu, Jinqiu; Yang, Yankang; Hao, Tianyu; Zhu, Lei; Zhou, Libo; Zhu, Haiming; Zou, Yecheng; Wei, Gang; Zhang, Yongming; Liu, Feng
Abstract : The spontaneous carrier generation process was identified in the Y6 acceptor with moderate quantum yields and extremely low recombination in optimized blends, which result in high efficiency and morphology tolerance. Abstract : The current research reveals the unique photo physical properties and carrier generation mechanisms of high efficiency non-fullerene acceptor-based organic photovoltaic blends. The analysis of device performance, morphology, and photo physics reveals that the interface carrier generation cannot support the device's current output. It is seen that primary photon excitons can dissociate into charge carriers in Y6, which displays a time scale of ∼0.3 ps with polaron yields above 28% in neat and blended thin films. This characteristic in combination with a large exciton diffusion length enables high morphology tolerance in Y6-overloaded blends. The carrier generation process is also combined with recombination studies. The recombination rate quantified by flux-dependent transient absorption measurements yields less than 5% total recombination and nearly 0% geminate recombination. These results define the advantages of the Y6 non-fullerene acceptor (NFA) and reveal the fundamental importance of developing new NFA materials with superior photo physical properties.